Engineering a high-affinity peptide binding site into the anti-CEA mAb M5A. Issue 6 (19th April 2017) - Zer, Cindy; Avery, Kendra N.; Meyer, Kassondra; Goodstein, Leah; Bzymek, Krzysztof P.; Singh, Gagandeep; Williams, John C.
Abstract: We have previously identified a cyclic peptide called meditope which binds to the central cavity of the Fab portion of cetuximab and shown that this peptide binding site can be grafted, or 'meditope-enabled', onto trastuzumab. This peptide has been shown to act as a hitch for the non-covalent attachment of imaging agents to meditope-enabled antibodies. Herein, we explore the process of grafting this peptide binding site onto M5A, an anti-CEA antibody in clinical trials for cancer diagnostics. In order to explore the contributions of the amino acids, we sequentially introduced pairs of amino acid substitutions into the Fab and then we reverse-substituted key residues in the presence of the other substitutions. We demonstrate that Pro40Thr, Gly41Asn, Phe83Ile and Thr85Asp in the light chain are sufficient to recreate the meditope binding site in M5A with single-digit micromolar affinity. We show that Pro40 abrogates peptide binding in the presence of the other 12 residue substitutions, and that the presence of all 13 substitutions does not interfere with antibody:antigen recognition. Collectively, these studies provide detailed insight for defining and fine-tuning the binding affinity of the meditope binding site within an antibody.